DETECTION OF DAY ANOMALIES AND ITS EFFECT; AN APPLICATION IN BIST FOOD INDEX - Murat Erdogan; Aykan Burak Bolat; Eda Oruç Erdoğan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The market efficiency approach is a knowledge-based approach and assumes that if the market is efficient, the information entering the market is effective at the price level. However, it is revealed in studies conducted at different times that markets that have existed have not always been effective on the basis of this view. On the basis of this definition, price anomalies that occur in case of deviation from the existing efficiency in the markets are defined as price anomalies in the literature. This study aims to determine the relationship between the stock returns of the companies traded in the stock market and included in the Food index and the days of the week. For this purpose, the stock returns of 10 companies in the BISTGIDA index whose uninterrupted data for between the years 1999-2019 were accessed and evaluated through panel data analysis. In this study, while the returns calculated over the daily closing prices of the firms were determined as the dependent variable, the traded days of the week were determined as the independent variable. According to the results of the analysis of the panel data analysis, it was concluded that Monday has a negative effect at the 1% significance level on the returns of the businesses included in the food index.